2015
DOI: 10.1080/13674676.2015.1038229
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual barriers to humility: a multidimensional study

Abstract: Many spiritual and religious traditions view spiritual pride as contrary to humility; however, the rising empirical research on spirituality and humility has involved limited investigation of the variety of spiritual barriers that inhibit a humble disposition. The present study investigated three distinct spiritual barriers (spiritual grandiosity, insecure attachment to God, and hunger for idealisation) as independent predictors of dispositional humility among graduate trainees in the helping professions (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Specifically, we found that changes in differentiation and humility were conditional upon lower initial levels of their respective scores, and conditional upon lower initial levels of insecure God attachment. These findings suggest that greater felt insecurity may inhibit change, consistent with prior findings of associations between greater insecure God attachment and (a) lower humility (e.g., Jankowski et al, 2019; Jankowski & Sandage, 2014a; Sandage et al, 2015) and (b) lower differentiation (Jankowski et al, 2019; Jankowski & Sandage, 2014a). These findings are also consistent with the secure base function of attachment, that is, less felt security can inhibit exploration and growth (Bell, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, we found that changes in differentiation and humility were conditional upon lower initial levels of their respective scores, and conditional upon lower initial levels of insecure God attachment. These findings suggest that greater felt insecurity may inhibit change, consistent with prior findings of associations between greater insecure God attachment and (a) lower humility (e.g., Jankowski et al, 2019; Jankowski & Sandage, 2014a; Sandage et al, 2015) and (b) lower differentiation (Jankowski et al, 2019; Jankowski & Sandage, 2014a). These findings are also consistent with the secure base function of attachment, that is, less felt security can inhibit exploration and growth (Bell, 2009).…”
Section: Discussionsupporting
confidence: 87%
“…For example, Hill et al (2016) note that humility 'requires a sense of security and enduring personal worth' (p. 119). Sandage et al (2015) note some earlier research on 'healthy attachment' shows that attachment can 'prepare a person to transcend the ego' (p. 209). Interestingly, general humility is also thought to be a basis for security and meaning: humility has been called a 'quiet virtue' (Lavelock et al, 2014), in the sense that it provides a foundation for selfacceptance as well as freedom from harmful social comparison and concern for status.…”
Section: What Factors Support and Undermine Intellectual Humility?mentioning
confidence: 98%
“…La Rochefoucauld thought people live with considerable ignorance and obscurity about their actual motives and intentions, meaning that actors may be oblivious to the artifice of their own humble pretense. Recently, Sandage et al (2015) pointed out that religious practices can induce 'delusional humility,' where arrogant people believe they are humble (p. 214). That phenomenon is not confined exclusively to religious believers, of course.…”
Section: Consensus Among Judges On Relational Humility Can Indicate Whatmentioning
confidence: 99%
See 1 more Smart Citation
“…As a foundational virtue and tenet in many religions, humility is often associated with religious processes. On the intrapersonal level, humility is associated with lower levels of psychological struggle with God (Grubbs & Exline, 2014), lower levels of spiritual grandiosity, and lower rates of insecure attachment (Sandage et al, 2015). On the interpersonal level, humility is associated with religiosity, generosity (Exline & Hill, 2012), compassion (Krause & Hayward, 2014), and spiritual support (Krause, 2012).…”
Section: Humility and Religionmentioning
confidence: 99%